Market Turmoil and IPO Listings: The Effect of Volatility in ‎The Indian Market - Shetty, Chetan; P, Vinish; T. , Nayana; B N, Bhagyalakshmi; C M, Charithra (International Journal of Accounting and Economics Studies, 2025)
IPOs are essential for companies to raise capital and offer growth potential to investors. Despite global uncertainties and liquidity challenges, ‎IPO activity is expected to rebound, driven by stronger momentum and larger deals. This study analyzes factors influencing IPO listing ‎prices in the Indian stock market from 2020 to 2024, a period marked by global disruptions and domestic political changes. Using data from ‎‎271 IPOs, the study explores the impact of macroeconomic factors, IPO-specific variables, and secondary market conditions. Multiple linear ‎regression shows that GDP growth, IPO size, subscription rates, and P/E ratios positively affect listing prices, while higher interest rates ‎have a negative impact. Larger IPO sizes and higher subscription rates further reflect strong investor confidence and demand. Market volatility and index performance have minimal direct effects, suggesting their influence may be mediated by other factors. These findings offer ‎insights for policymakers, companies, and investors navigating IPO markets‎.